Modulation of amyloid states by molecular chaperones - Wentink, Anne; Nussbaum-Krammer, Carmen; Bukau, Bernd (Cold Spring Harbor perspectives in biology, 2019)
Aberrant protein aggregation is a defining feature of most neurodegenerative diseases. During pathological aggregation, key proteins transition from their native state to alternative conformations, which are prone to oligomerize into highly ordered fibrillar states. As part of the cellular quality control machinery, molecular chaperones can intervene at many stages of the aggregation process to inhibit or reverse aberrant protein aggregation or counteract the toxicity associated with amyloid species. Although the action of chaperones is considered cytoprotective, essential housekeeping functions can be hijacked for the propagation and spreading of protein aggregates, suggesting the cellular protein quality control system constitutes a double-edged sword in neurodegeneration. Here, we discuss the various mechanisms used by chaperones to influence protein aggregation into amyloid fibrils to understand how the interplay of these activities produces specific cellular outcomes and to define mechanisms that may be targeted by pharmacological agents for the treatment of neurodegenerative conditions.
Gesehen am 06.08.2019